Problem video gaming in adolescents: An examination of the Pathways Model. Issue 2 (4th May 2022) - Marchica, Loredana A.; Richard, Jérémie; Nower, Lia; Ivoska, William; Derevensky, Jeffrey L.
ABSTRACT: Problem video gaming (PVG) is of significant concern among youth and contributes to increases in mental health issues among adolescents. Prevalence rates for PVG are estimated at 1-3% among non-clinical samples. Like problem gambling, it has been hypothesized that individuals reporting PVG are part of a heterogeneous group with different profiles, dependent on specific psychosocial factors. Identifying these profiles allows clinicians to create targeted interventions. The following preliminary study aimed to identify the emotional and behavioral characteristics that distinguish between subgroups of adolescents reporting PVG and how these subgroups compare to those proposed by the Pathways Model. The study included a cross-sectional sample of 288 adolescents reporting PVG  from a Midwestern state. Measures included the Ohio Problem Severity Scales, the Internet Gaming Disorder Scale-SF, and frequency of video gaming. A latent class analysis identified four classes which aligned with the subgroups proposed by the Pathways Model (i.e . behavioral conditioned, emotionally vulnerable, and antisocial/impulsivist), and two additional classes which could be considered as milder variants of the emotionally vulnerable and antisocial/impulsivist groups. These results suggest that adolescents reporting PVG form a heterogeneous group, with each profile requiring different considerations in developing targeted interventions. Implications for prevention and future research are discussed.